(untitled) (Al-Farooq Journal of Sciences, 2026)
This study aimed to explore the use of cloud computing and its impact on the quality of higher education from the perspective of faculty members. It was conducted as a field study at the Libyan Academy for Postgraduate Studies – Janzour. To achieve the study’s objectives, a main hypothesis was formulated: "There is a statistically significant impact between the use of cloud computing and the quality of higher education at the Libyan Academy." To collect the necessary data, a structured questionnaire was designed. The data were analyzed using the Statistical Package for the Social Sciences (SPSS - v.26), and the reliability and validity of the instrument were verified. The study population consisted of faculty members at the Academy, totaling )286(individuals. A sample of )117(was selected, from which 99 fully completed and analyzable questionnaires were retrieved, yielding an overall response rate of )%.84.6( The study reached several key findings, most notably the existence of a statistically significant impact of cloud computing usage on the quality of higher education, as perceived by faculty members at the Libyan Academy for Postgraduate Studies – Janzour, Tripoli. Furthermore, the study revealed a statistically significant direct impact of specific dimensions of cloud computing—namely infrastructure, educational software, ease of use, and information security—on the quality of higher education, from the faculty’s perspective. Based on these findings, the study recommends that the Libyan Academy prioritize its digital transformation initiative and integrate cloud computing into its strategic institutional planning.